1997
DOI: 10.1021/jo970600p
|View full text |Cite
|
Sign up to set email alerts
|

Diastereofacial Selectivity in Reactions of 5-Substituted (X) Adamant-2-yl Cations:  Manifestations of Electron Demand

Abstract: A series of 5-substituted (X) 2,2-dimethoxyadamantanes (4, X ) F, Cl, Br, COOCH 3 , OCH 3 , CH 3 , C 6 H 5 , p-NO 2 C 6 H 4 , p-BrC 6 H 4 , SiMe 3 , and SnMe 3 ) as well as 2-methylene-5-tert-butyladamantane (6, Y ) CH 2 ; X ) C(CH 3 ) 3 ) have been synthesized and characterized. Reduction of the ketals 4 under ionic conditions with triethylsilane and phenylsilane provide π-facial diastereoselectivities for hydride trapping of 5-substituted (X) 2-methoxyadamant-2-yl cations (1, R ) OCH 3 T 5). A comparison of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
1

Year Published

1998
1998
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 33 publications
3
34
1
Order By: Relevance
“…Although these groups are similar in that they exert virtually no electrostatic field influence (σ F ≈ 0; Table ) they differ markedly with respect to their double hyperconjugative interaction mode as revealed by the 19 F SCS of 14 and 23 (Tables and , respectively). Model system reactivity studies (see later) under conditions of high electron demand have confirmed and heightened this distinction. 63i,,, Note, however, that the selectivities exerted by these groups (Tables and ) are feeble and, moreover, the observed selectivities are in accord with expectations based purely on electrostatic grounds. Thus, the overall picture portrayed by the results (Tables and ), namely, the unimportance of transition-state hyperconjugation governing diastereofacial selectivity in the nucleophilic additions of 1 (Y = O), is strongly reinforced.…”
Section: Diastereofacial Selectivitymentioning
confidence: 73%
See 3 more Smart Citations
“…Although these groups are similar in that they exert virtually no electrostatic field influence (σ F ≈ 0; Table ) they differ markedly with respect to their double hyperconjugative interaction mode as revealed by the 19 F SCS of 14 and 23 (Tables and , respectively). Model system reactivity studies (see later) under conditions of high electron demand have confirmed and heightened this distinction. 63i,,, Note, however, that the selectivities exerted by these groups (Tables and ) are feeble and, moreover, the observed selectivities are in accord with expectations based purely on electrostatic grounds. Thus, the overall picture portrayed by the results (Tables and ), namely, the unimportance of transition-state hyperconjugation governing diastereofacial selectivity in the nucleophilic additions of 1 (Y = O), is strongly reinforced.…”
Section: Diastereofacial Selectivitymentioning
confidence: 73%
“…The calculated diastereoselectivities for electrophilic addition (HCl in CH 2 Cl 2 ) to 1 (Y = CH 2 ) based on the ρ FS value from Figure are listed in Table together with the experimentally observed product distributions. , It can be seen that there is a quite good agreement between the observed and calculated polar-field-induced selectivities in CH 2 Cl 2 for most of the σ-electron-withdrawing substituents. Thus, the main conclusion to be drawn from these results is that the electrostatic field effect (σ F effect) of these groups plays an important role governing diastereoselectivity in the capture of 32 (R = CH 3 , X = σ-electron-withdrawing group).…”
Section: B Nucleophilic Capture Of 5-substituted (X) 2-adamantyl Cati...mentioning
confidence: 76%
See 2 more Smart Citations
“…Subsequently, the study was extended to a variety of other substrates related to 22 . Diastereoselectivity was also examined in other types of reactions, such as epoxidation and dichlorocarbene addition, solvolysis, thermal 86 and photocycloadditions, cycloreversion, oxidation, oxy-Cope 90 and Claisen 91 rearrangements, protonation, radical capture, and iron tricarbonyl complexation . The remote substituent effects in all of these diverse reactions were qualitatively similar.…”
Section: Nucleophilic Additions To Carbonyl Groupsmentioning
confidence: 99%